Locomotion and basicranial anatomy in primates and marsupials. Issue 111 (October 2017) - Villamil, Catalina I.
Abstract: There is ongoing debate in paleoanthropology about whether and how the anatomy of the cranium, and especially the cranial base, is evolving in response to locomotor and postural changes. However, the majority of studies focus on two-dimensional data, which fails to capture the complexity of cranial anatomy. This study tests whether three-dimensional cranial base anatomy is linked to locomotion or to other factors in primates ( n = 473) and marsupials ( n = 231). Results indicate that although there is a small effect of locomotion on cranial base anatomy in primates, this is not the case in marsupials. Instead, facial anatomy likely drives variation in cranial base anatomy in both primates and marsupials, with additional roles for body size and brain size. Although some changes to foramen magnum position and orientation are phylogenetically useful among the hominoids, they do not necessarily reflect locomotion or positional behavior. The interplay between locomotion, posture, and facial anatomy in primates requires further investigation.